Limnological Notes on Ramsagar, Dinajpur, Bangladesh (Bangladesh Journal of Botany, 2012)
Ramsagar, an artificial lake of Dinajpur district has been investigated limnologically. Mean alkalinity, DO, pH, TDS and conductivity of the lake were 0.50 meq/l, 7.99 mg/l, 6.73, 10.66 mg/l and 73.66 ?S/cm, respectively. The concentration of soluble reactive phosphorus and silicate was very low. Mean value of the former parameter was 3.16 ?g/l and the latter was 0.77 mg/l. Nitrate-nitrogen concentration was < 0.1 mg/l. Phytoplankton biomass as chl a was 5.92 ?g/l and that of phaeopigment 3.65 ?g/l. Phytoplankton flora of the lake was found to be dominated by desmids. The dominant species were Staurastrum coarctatum var. subcurtum (59.35×104, ind/l); S. subgracillimum var. tortum (44.83×104 ind/l) and S. leptacanthum (29.06×104 ind/l). Among the blue-green algae, Anabaena utermöhlii was dominant. Chlorococcales was represented by seven species. The total density of phytoplankton was 163.53×104 ind/l. Considering the overall limnological characteristics, the lake could be characterized as acidic and nutrient poor.DOI: http://dx.doi.org/10.3329/bjb.v41i1.11091 Bangladesh J. Bot. 41(1): 119-121, 2012 (June)